Interdependent group contingency to promote physical activity in children - Foote, Catherine; Bray, Melissa A.; Kehle, Thomas J.; VanHeest, Jaci L.; Gelbar, Nicholas W.; Byer-Alcorace, Gabriel; Maykel, Cheryl; DeBiase, Emily (Canadian Journal of School Psychology, 2017)
As the number of children affected by obesity increases in the United States, it is necessary to intervene with preventive and intervention techniques that will enact change. Because children spend a significant amount of their time in school, it is of particular interest to target strategies during the school day. Given the recommendations for the total duration and intensity of physical activity children should participate in, recess period is a means of acquiring a portion of this daily recommendation. Contingent reinforcement is a technique that is consistently used in schools to promote behavior change. One of these techniques, group contingencies, has repeatedly been shown to increase desired behavior and decrease inappropriate behavior in schools. In the present study, a multiple baseline design was utilized to investigate the use of interdependent group contingencies in physical activity performance during recess, as measured by pedometers, with one class from each of the third, fourth, and fifth grades at an elementary school. Some of the variability existed in gender- and body mass index-specific (BMI) subgroups, in regard to the effectiveness of the intervention and continued maintenance of increased physical activity levels, following the removal of the intervention. However, the overall results support the use of an interdependent group contingency intervention to increase the amount of physical activity students engaged in during recess.
Keywords: dept.csp; exercise; obesity; school-based treatment

Do the kinds of achievement errors made by students diagnosed with ADHD vary as a function of their reading ability? - Pagirsky, Matthew S.; Koriakin, Taylor A.; Avitia, Maria; Costa, Michael; Marchis, Lavinia; Maykel, Cheryl; Sassu, Kari; Bray, Melissa A.; Pan, Xingyu (Journal of Psychoeducational Assessment, 2017)
A large body of research has documented the relationship between attention-deficit hyperactivity disorder (ADHD) and reading difficulties in children; however, there have been no studies to date that have examined errors made by students with ADHD and reading difficulties. The present study sought to determine whether the kinds of achievement errors made by students diagnosed with ADHD vary as a function of their reading ability. The participants in this study were 91 students in the ADHD clinical validity standardization sample of the Kaufman Test of Educational Achievement-Third Edition (KTEA-3), as well as a control group of 63 students selected from the larger standardization sample. Students with ADHD and reading difficulties demonstrated a statistically significant greater amount of errors across tests of academic achievement. Findings from the study are discussed within the context of past research, as well as implications for the field of school psychology and practitioners.
Keywords: achievement; attention-deficit hyperactivity disorder; dept.csp; reading; special education

Biological gender differences in students’ errors on mathematics achievement tests - Stewart, Christie; Root, Melissa M.; Koriakin, Taylor; Choi, Dowon; Luria, Sarah R.; Bray, Melissa A.; Sassu, Kari; Maykel, Cheryl; O’Rourke, Patricia; Courville, Troy (Journal of Psychoeducational Assessment, 2017)
This study investigated developmental gender differences in mathematics achievement, using the child and adolescent portion (ages 6-19 years) of the Kaufman Test of Educational Achievement-Third Edition (KTEA-3). Participants were divided into two age categories: 6 to 11 and 12 to 19. Error categories within the Math Concepts & Applications and Math Computation subtests of the KTEA-3 were factor analyzed and revealed five error factors. Multiple ANOVA of the error factor scores showed that, across both age categories, female and male mean scores were not significantly different across four error factors: math calculation, geometric concepts, basic math concepts, and addition. They were significantly different on the complex math problems error factor, with males performing better at the p ¡ .05 significance level for the 6 to 11 age group and at the p ¡ .001 significance level for the 12 to 19 age group. Implications in light of gender stereotype threat are discussed.
Keywords: KTEA-3; achievement; dept.csp; error analysis; factor analysis; gender; math